Understanding biological impacts of ENSO on the eastern Pacific: an evolving scenario. (6th June 2008) - Camus, Patricio A.
The understanding of the physical nature of the El Nino Southern Oscillation (ENSO) phenomenon has gone through significant and progressive changes during the last decades. Such advances lead biologists to deal with an increasingly complex view of the impacts of ENSO events on coastal marine systems, facing an ever-evolving perspective of the physical setting in which natural populations and communities develop and persist. This paper discusses how the increasing understanding of ENSO has changed our perception of its nature as a biological disturbance regime, and therefore, our way of conceptualising and studying its impacts under different ecological contexts. The analysis emphasises common problems derived from the misuse of before?after and correlational approaches, and stresses the need for proper and more accurate information to improve our perspective of ENSO impacts, providing study cases from rocky intertidal communities in northern Chile.